Indigenous Literatures at the Crossroads of Languages: Approaches and Avenues - Brouwer, Malou (Alternative francophone)

(untitled) (University of Alberta, Department of Modern Languages and Cultural Studies, 2023)
This article examines critical discourses and approaches for the study of Indigenous literatures across languages. On the one hand, it investigates how the French-English divide is challenged by Indigenous authors and how it has been and can be further dealt with in Indigenous literary studies (ILS). On the other hand, it pays attention to the centrality and revitalization of Indigenous languages as they challenge colonial languages, complicate the French-English divide in ILS, and center Indigenous experiences. Engaging with the question “what approaches can scholars, teachers, and students in Indigenous literary studies use for the study of Indigenous literatures at the crossroads of languages?”, I highlight multilingual work by Indigenous authors, collect resources that directly engage Indigenous literatures from a (multi)language perspective, and gather approaches that can be helpful in developing a framework for the study of the multilingual corpus of Indigenous literatures.